Physicians' knowledge, attitudes, and perceptions concerning antibiotic resistance: a survey in a Ghanaian tertiary care hospital - Appiah-Korang Labi; Noah Obeng-Nkrumah; Stephanie Bjerrum; Nii Armah Adu Aryee; Yaw Adjei Ofori-Adjei; Alfred E. Yawson; Mercy J. Newman (BMC, 2018)
Abstract Background Understanding the knowledge, attitudes and practices of physicians towards antibiotic resistance is key to developing interventions aimed at behavior change. The survey aimed to investigate physicians' knowledge and attitudes towards antibiotic resistance in a tertiary-care hospital setting in Ghana. Methods We conducted a cross-sectional respondent-driven survey using a 40-item, anonymous, voluntary, traditional paper-and-pencil self-administered questionnaire among 159 physicians at Korle-Bu Teaching Hospital. Single and multi-factor analysis were conducted to assess the study objectives. Results The survey was completed by 159 of 200 physicians (response rate of 79.5%). Of physicians, 30.1% (47/156) perceived antibiotic resistance as very important global problem, 18.5% (29/157) perceived it as very important national problem and only 8.9% (14/157) thought it as a very important problem in their hospital. Methicillin resistant Staphylococcus aureus was the most known about antibiotic resistant bacteria of public health importance followed by extended-spectrum beta-lactamase-producing Enterobacteriaceae, carbapenem resistant Enterobacteriaceae (CRE) and vancomycin resistant enterococci (VRE). In multiple logistic regression analysis, senior physicians were nearly 3 times more likely to know about CRE than junior physicians. The odds of knowing about VRE increased over 4.5 times from being a junior to becoming senior physician. Among junior physicians, age had no associated effect on their knowledge of VRE or CRE. Conclusions Physicians in this survey showed variable knowledge and perceptions on antibiotic resistance. Introducing educational programs on antibiotic resistance would be a useful intervention and should focus on junior physicians.